(untitled) (Studia Prawnicze / The Legal Studies, 1983)
In the present article the notion of "law and order" from the point of view of administrative law and related notions "public safety" and "public peace" have been defined and discussed. ’The notions were not defined and characterized in the Polish literature on administrative law in the post-war period. The notion of law and order (and related notions) are reconstructed from the provisions of administrative law, considering also the practice a protection of law and order and public safety in Our country. All elements, of the above rnetiioned notions arc described in details in the present article: moreover, the problems of protection of law and order, public safety and peace which are systemically connected with those notions have also been presented. The author thinks that the description and explanation of the above mentioned notions on the basis of administrative law may be of a paramount importance in establishing, i.a., Object of protection by administrative law, sphere of activity of state organs and their competence, general clauses necessary for proper implementation and execution of provisions of administrative law as well as of a theoretical importance.